2018
DOI: 10.1007/s00268-018-4837-x
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomania? The Inapplicability of Sarcopenia Measurement in Predicting Incisional Hernia Development

Abstract: Background Incisional hernia is a frequent complication after abdominal surgery. A risk factor for incisional hernia, related to body composition, is obesity. Poor skeletal muscle mass might also be a risk factor, as it may result in weakness of the abdominal wall. However, it remains unknown if sarcopenia (i.e. low skeletal muscle mass) is a risk factor for incisional hernia. Therefore, this study aims to investigate whether a relation between sarcopenia and incisional hernia exists. Methods Patients from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 51 publications
3
25
0
Order By: Relevance
“…Van Rooijen and colleagues recently published their series describing the development of ventral hernia after incisional laparotomy for oncologic surgery and demonstrated no predictive value of sarcopenia while commenting on the inherent selection bias, which occurs when selecting patients for a clinical trial and that obviously frail and/or deconditioned patients were not offered surgery and/or elected not to participate. 30 Similar findings have been seen in the elective spine surgery literature. It should be noted that aside from the presence of rheumatologic disease and a slightly lower, yet physiologically normal BMI, there was no obvious phenotypic evidence of sarcopenia in the breast cancer patients included in this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Van Rooijen and colleagues recently published their series describing the development of ventral hernia after incisional laparotomy for oncologic surgery and demonstrated no predictive value of sarcopenia while commenting on the inherent selection bias, which occurs when selecting patients for a clinical trial and that obviously frail and/or deconditioned patients were not offered surgery and/or elected not to participate. 30 Similar findings have been seen in the elective spine surgery literature. It should be noted that aside from the presence of rheumatologic disease and a slightly lower, yet physiologically normal BMI, there was no obvious phenotypic evidence of sarcopenia in the breast cancer patients included in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results have been seen in other published series where the presence of sarcopenia does not predict certain postoperative complications in elective surgery. Van Rooijen and colleagues recently published their series describing the development of ventral hernia after incisional laparotomy for oncologic surgery and demonstrated no predictive value of sarcopenia while commenting on the inherent selection bias, which occurs when selecting patients for a clinical trial and that obviously frail and/or deconditioned patients were not offered surgery and/or elected not to participate 30 . Similar findings have been seen in the elective spine surgery literature.…”
Section: Discussionmentioning
confidence: 73%
“…Univariate analysis for an increased risk of SSO demonstrated a significant association with obesity, preoperative RT, hypertension, and bilateral component separation ( abdominis release and should be considered whenever possible. [27][28][29] Similar to Rooijen et al 30 our study demonstrated that obesity had a greater impact on hernia occurrence and SSOs than sarcopenia.…”
Section: Surgical Site Occurrencesupporting
confidence: 88%
“…Sarcopenia is of increasing clinical interest in a number of complex surgical specialties, including surgical oncology, transplant surgery, trauma, emergency, and vascular surgery [1][2][3][4][5][6][7][8][9][10]. Sarcopenia is defined as a loss of skeletal muscle mass, with an associated reduction in muscle strength and functional capacity [11][12][13]. Recent studies have identified sarcopenia as an independent predictor of poor postoperative outcomes following major abdominal surgery, particularly in patients undergoing oncological resection.…”
Section: Introductionmentioning
confidence: 99%